2017
DOI: 10.1007/s00415-016-8374-y
|View full text |Cite
|
Sign up to set email alerts
|

Global and regional annual brain volume loss rates in physiological aging

Abstract: The objective is to estimate average global and regional percentage brain volume loss per year (BVL/year) of the physiologically ageing brain. Two independent, cross-sectional single scanner cohorts of healthy subjects were included. The first cohort (n = 248) was acquired at the Medical Prevention Center (MPCH) in Hamburg, Germany. The second cohort (n = 316) was taken from the Open Access Series of Imaging Studies (OASIS). Brain parenchyma (BP), grey matter (GM), white matter (WM), corpus callosum (CC), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
43
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 38 publications
10
43
1
3
Order By: Relevance
“…ml/year to the ICV at age 20 years that is replaced by a decrease of 1.3 ml/year at age 55. Interestingly, the decade of life where we found the ICV to change direction between growth and decline corresponds well to the decade of life where the amount of white matter in the brain stop growing and starts shrinking or stats accelerated shrinking [37,38,36]. This raises the possibility that these two processes result from a shared genetic cause, which will be interesting hypothesis to check in future works.…”
supporting
confidence: 66%
“…ml/year to the ICV at age 20 years that is replaced by a decrease of 1.3 ml/year at age 55. Interestingly, the decade of life where we found the ICV to change direction between growth and decline corresponds well to the decade of life where the amount of white matter in the brain stop growing and starts shrinking or stats accelerated shrinking [37,38,36]. This raises the possibility that these two processes result from a shared genetic cause, which will be interesting hypothesis to check in future works.…”
supporting
confidence: 66%
“…The ideal modeling of There is evidence that nonparametric approaches may be advantageous in certain instances. [40][41][42] With only 2 measurements (baseline, follow-up) in the present study, we decided to calculate a simple volume difference for each patient (corresponding to a linear fit) and to determine the mean volume change in the cohort by averaging the patients' results. We deliberately refrained from applying more sophisticated nonlinear models for fitting volume changes because they would only be sufficiently supported by more than 2 measurements in time.…”
Section: Discussionmentioning
confidence: 99%
“…Several cross-sectional (Fjell, et al, 2009, Fjell, et al, 2013, Marcus, et al, 2007, Schippling, et al, 2017, Ziegler, et al, 2012, as well as longitudinal studies (Driscoll, et al, 2009, Hedman, et al, 2012, Marcus, et al, 2010, Taki, et al, 2011, found that BVL critically depends on age, in both, MS patients and healthy individuals. A recent study reported age dependent mean BVL per year values in physiological aging (Schippling, et al, 2017). However, the data in that study were extrapolated from cross-sectional brain volumetry data using a non-parametric fitting approach.…”
Section: Introductionmentioning
confidence: 99%
“…However, the data in that study were extrapolated from cross-sectional brain volumetry data using a non-parametric fitting approach. As discussed before (Schippling, et al, 2017), cross-sectional data allows the determination of mean BVL per year values of a given cohort, but lacks estimates of the biological variability (age-dependent standard deviations) of BVL per year values for a specific age range. To interpret BVL per year in disease models correctly, it is of utmost importance to do so against the background of measurements derived from longitudinal studies in healthy aging populations, to allow a correction for physiological aging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation